Chlorella sp. and Nannochloropsis sp. Inclusion in Plant-Based Diets Modulate the Intestine and Liver Antioxidant Mechanisms of European Sea Bass Juveniles - Castro, Carolina; Coutinho, Filipe; Iglesias, Paula; Oliva-Teles, Aires; Couto, Ana (Frontiers in Veterinary Science, 2020)
This study aimed to evaluate the effects of including microalgae Chlorella sp. or Nannochloropsis sp. in plant-based diets on antioxidant mechanisms of European sea bass (Dicentrarchus labrax) juveniles. For this purpose, three isoproteic (50%) and isolipidic (19%) diets were formulated: a practical diet, containing 15% fish meal (FM) and plant ingredients as the protein source and a mixture of fish oil and vegetable oils (40: 60) as lipid source (control diet); and two diets identical to the control but with the FM replaced by Nannochloropsis sp. or Chlorella sp. (diets Nanno and Chlo, respectively). The diets were offered to quadruplicate groups of 25 fish (initial body weight: 24± 1 g) for 11 weeks and then enzymatic and non-enzymatic antioxidant mechanisms and lipid oxidative biomarkers were assessed in the liver and intestine of these fish. Results showed that the antioxidant response was tissue-dependent, with the liver exhibiting lower glutathione peroxidase and glucose-6-phosphate dehydrogenase (only in Chlo group) activities, and intestine lower superoxide dismutase activity with the diets including microalgae compared to control diet. An increase of oxidized glutathione content was also observed in the intestine of fish fed the microalgae diets. Catalase and glutathione reductase activities, oxidative stress index, and total and reduced glutathione, were unaffected by dietary treatments in both tissues. Overall, the lipid peroxidation status was not compromised by the replacement of FM by microalgae.